2013
DOI: 10.1002/jhm.2064
|View full text |Cite
|
Sign up to set email alerts
|

Choosing wisely in pediatric hospital medicine: Five opportunities for improved healthcare value

Abstract: BACKGROUND Despite estimates that waste constitutes up to 20% of healthcare expenditures in the United States, overuse of tests and therapies is significantly under‐recognized in medicine, particularly in pediatrics. The American Board of Internal Medicine Foundation developed the Choosing Wisely campaign, which challenged medical societies to develop a list of 5 things physicians and patients should question. The Society of Hospital Medicine (SHM) joined this effort in the spring of 2012. This report provides… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
126
1
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 190 publications
(134 citation statements)
references
References 53 publications
1
126
1
2
Order By: Relevance
“…Our work is also, to our knowledge, the first published improvement project targeting the Pediatric Hospital Medicine Choosing Wisely recommendations. 12 Despite reduction in time spent on CPOx, there was no change in time until medically ready. Although an earlier study suggested CPOx prolonged LOS, our findings are consistent with preliminary results of a randomized trial comparing IPOx and CPOx, which did not show reduced LOS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our work is also, to our knowledge, the first published improvement project targeting the Pediatric Hospital Medicine Choosing Wisely recommendations. 12 Despite reduction in time spent on CPOx, there was no change in time until medically ready. Although an earlier study suggested CPOx prolonged LOS, our findings are consistent with preliminary results of a randomized trial comparing IPOx and CPOx, which did not show reduced LOS.…”
Section: Discussionmentioning
confidence: 99%
“…3 Studies in adults have also highlighted the contribution of CPOx to alarm counts on units, [4][5][6][7][8] which the Joint Commission has emphasized as a patient safety issue. 9,10 Despite evidence highlighting the limitations and lack of value, CPOx 12 emphasizing the lack of evidence and waste involved in its widespread use. In 2009, asthma and bronchiolitis accounted for ∼260 000 admissions and $3.2 million in hospital charges.…”
Section: Discussionmentioning
confidence: 99%
“…26,27 Newborn medicine offers special challenges to the Choosing Wisely approach. Neonatal care is provided by an interprofessional team through which a family's influence has been somewhat indirect.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, the majority of the pediatric Choosing Wisely initiatives decrease opportunities for overdiagnosis, with recommendations that limit the use of CT scans, MRI, chest radiographs, apnea monitors, food allergy screening, and continuous pulse oximetry. 72,73 In general, guidelines that endorse testing can address the harms of overdiagnosis and support strong recommendations for testing with evidence that important outcomes for children are improved by diagnosis. Use of the US Preventive Services Task Force analytic framework, which considers both harms and benefits and clearly delineates pertinent outcomes, would help guideline panels in this endeavor.…”
Section: The Way Forwardmentioning
confidence: 99%